Evaluating ESG information disclosure quality and integrated firm value: A bibliometric review - Yixuan, Chen; Aziz, Nazirah; Kharuddin, Khairul Ayuni Mohd (Edelweiss Applied Science and Technology, 2025)
The importance of disclosure related to environmental, social, and governance (ESG) factors is increasingly recognized. The aim of this research is to fill gaps in the literature regarding the quality of ESG disclosures and to advocate for a broader perspective in assessing corporate value. To gain a deeper understanding of developments in ESG aspects and emerging areas for future research, this study conducted a bibliometric analysis of current literature in the Web of Science (WOS) database, utilizing VOSviewer and CiteSpace tools for analysis to identify gaps in the literature and reveal trends. This study identifies a significant gap in the literature concerning the quality of ESG disclosures. Furthermore, most studies have focused on stakeholder theories; it is important for researchers to continually explore different theoretical frameworks to support their findings. Present studies have linked ESG performance with financial performance, but few investigate comprehensive values such as social or environmental value. It is also crucial to consider economic externalities when evaluating the impact of ESG reporting, especially given the potential for ESG washing. As ESG factors become increasingly vital to corporate strategy and stakeholder engagement, it is essential to improve clarity around definitions, measurement, and evaluation metrics related to ESG performance.